Effect of Oxidative Sardin Fish Oil for Food Utilization - Pitria Andriyani; Tati Nurhayati; Sugeng Heri Suseno (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Sardine is an economic fish industry product in Indonesia. Sardin fish oil of fish meal by-product can be processed into ethyl ester as a food grade product. The purpose of this study were to determine the chemical and physical the best ethyl ester of Semirefined and refined oil from sardine fish meal by-products. Results showed that heavy metals detected was cadmium (Cd) value, i.e. 0.02 ppm. SFA content of crude oil sardines was 29.39% with palmitic acid (16.24%) as the predominant fatty acids. The MUFA content amounted to 14.87% with palmitic acid as the predominant fatty acid (5.76%). The PUFA content were 35.47% with DHA (17.07%) as the predominant fatty acid, while EPA amounted to 13.82%. Semirefined oil transformed into Semirefined ethyl ester oil was the best on oxidative and physical parameters. Oxidation process produced Semirefined ethyl ester with 1.50±0.00 mEq/kg peroxide value (PV), 0.90±0.15% fattyacids (% FFA), 5.46±0.32 mEq/kg Anisidin p-value (p-AV), 8.46±0.32 mEq/kg oxidation (TOTOKS), 62.15±0.27%T viscosity and and 5.65±0,26 cP clarity.